Analysis of Needs for The Development of Viewing Skills, An Infographic Based on The Middle School Level - Sania Cahyani; Isah Cahyani; Yeti Mulyati (Universitas Muhammadiyah Malang, 2025)
Amid the massive development of visual media in 21st-century learning, viewing skills, especially in understanding infographics, are an essential competency that junior high school students must have. However, reality reveals that the learning process and available assessments have not adequately facilitated this ability. This study aims to analyse the necessity of developing an evaluation for infographic-based viewing skills to enhance the visual literacy of junior high school students. The research approach employs descriptive qualitative methods, including classroom observation techniques, in-depth interviews with teachers and students, and the analysis of learning documents. The data obtained were analysed thematically to reveal patterns of needs, obstacles, and opportunities for developing visual assessments in the school environment. The results indicated that teachers did not yet have an assessment tool that explicitly assessed students' visual abilities. In contrast, students showed weaknesses in interpreting visual elements such as icons, data structures, and colours in infographics. In addition, the curriculum and lesson plan have not explicitly integrated viewing skill indicators. This study concludes that there is an urgent need to develop integrative assessments that can bridge the gap between visual representation in learning and students' ability to interpret it critically. These findings greatly help improve visual literacy theory and teaching methods to address the challenges of using different media types in today's learning.